Ambivalent embrace : Jewish upward mobility in postwar America - Kranson, Rachel (The University of North Carolina Press, 2017)
"This new cultural history of Jewish life and identity in the United States after World War II focuses on the process of upward mobility. ... challenges the common notion that most American Jews unambivalently celebrated their generally strong growth in economic status and social acceptance during the booming postwar era. In fact, a significant number of Jewish religious, artistic, and intellectual leaders worried about the ascent of large numbers of Jews into the American middle class"--